2018
DOI: 10.4103/ijp.ijp_544_17
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of reporting of adverse drug reactions to oncology drugs: An experience from a national center of clinical excellence

Abstract: INTRODUCTION:Adverse drug reaction (ADR) is a public health problem which constitutes one of the leading causes of morbidity and mortality worldwide. In India, only a few studies reported cancer chemotherapy-induced ADRs. The objectives of the present study were to assess the organ system involved, frequency, severity, and preventability of the ADRs occurred.MATERIALS AND METHODS:Data on ADRs of retrospective cohorts were extracted from the filled ADR forms received from the department of radiation oncology. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
5
9
0
Order By: Relevance
“…Sharma PK et al 25 study showed that the more than two-thirds of the ADRs were related “possible” to the suspected oncology in causality assessment, mild in severity and the majority of them were preventable, which is consistent with the findings of this study. Out of 129 prescriptions, 13% of interactions were classified as “monitor therapy” (category C), with the majority of interactions being between Capecitabine and proton pump inhibitors (PPIs).…”
Section: Discussionsupporting
confidence: 91%
“…Sharma PK et al 25 study showed that the more than two-thirds of the ADRs were related “possible” to the suspected oncology in causality assessment, mild in severity and the majority of them were preventable, which is consistent with the findings of this study. Out of 129 prescriptions, 13% of interactions were classified as “monitor therapy” (category C), with the majority of interactions being between Capecitabine and proton pump inhibitors (PPIs).…”
Section: Discussionsupporting
confidence: 91%
“…Such effects have been reported in patients going under chemotherapy, immune check point inhibitor, program protein inhibitor (PD1) at the latter stage of treatment even after discontinuing the medicine. In these patients the symptoms of Alopecia (hair loss), skin patches, dermatitis eczema are observed (Sharma et al, 2018). The genes like Tnfrs19, Ercc2, Lama5, Ctsl, Per1 are shown to be involved in etiology of skin disorders, these genes regulate various biological process involved in hair follicle development, hair follicle maturation, hair follicle morphogenesis and regulation of hair cycle (Lim, Kim, Lim, & Kim, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…8 Although few studies pertaining to pharmacovigilance in cancer patients have been undertaken in the past, all were generally designed as snapshot studies with relatively little attention to a particular cancer and its associated risk factors in the target populations. [9][10][11][12] Therefore, the present study was planned among the oral cancer patients with the aim of providing them with tailored pharmacotherapy with fewer adverse effects and complications.…”
Section: Study Variablesmentioning
confidence: 99%